(untitled) (Journal of Mathematical Study, 2021)
Metric subregularity is an important and active area in modern variational analysis and nonsmooth optimization. Many existing results on the metric subregularity were established in terms of coderivatives of the multifunctions concerned. This note tries to give a survey of the metric subregularity theory related to the coderivatives and normal cones.